Fundamentals of Network Forensics A Research Perspective - Joshi, R.C; Pilli, Emmanuel S. (Computer Communications and Networks, 2016)
This timely text/reference presents a detailed introduction to the essential aspects of computer network forensics. The book considers not only how to uncover information hidden in email messages, web pages and web servers, but also what this reveals about the functioning of the Internet and its core protocols. This, in turn, enables the identification of shortcomings and highlights where improvements can be made for a more secure network. Topics and features: Provides learning objectives in every chapter, and review questions throughout the book to test understanding Introduces the basic concepts of network process models, network forensics frameworks and network forensics tools Discusses various techniques for the acquisition of packets in a network forensics system, network forensics analysis, and attribution in network forensics Examines a range of advanced topics, including botnet forensics, smartphone forensics, and cloud forensics Reviews a number of freely available and easily installable tools for performing forensic activities Researchers and students of network forensics will find this accessible work to provide an ideal technical foundation to the field. The focus on practically useful techniques and tools will also appeal to professional network forensic analysts involved in legal investigations. Prof. Ramesh Chandra Joshi is the Chancellor of Graphic Era University, Dehradun, India. He was formerly a Professor in the Department of Electronics and Computer Engineering at the Indian Institute of Technology Roorkee, India. Dr. Emmanuel Shubhakar Pilli is an Assistant Professor in the Department of Computer Science and Engineering at Malaviya National Institute of Technology, Jaipur, India.